Knowledge, attitude and behaviour regarding hepatitis C virus infection amongst Brazilian dental students - Souza, N. P. [UNESP]; Villar, L. M.; Moimaz, S. A.S. [UNESP]; Garbin, A. J.Í. [UNESP]; Garbin, C. A.S. [UNESP] (Wiley, 2017)
Aim: Dental health professionals, including dental students, are at high risk of exposure to infection with the hepatitis C virus (HCV) through occupational percutaneous injuries and eye exposure. Further, fear of HCV infection is associated with discriminatory attitudes. The current study aimed to evaluate the knowledge about HCV infection amongst dental students and their attitudes towards patients infected with HCV. Methods: A cross-sectional survey was conducted amongst 340 Brazilian dental students from two public universities using an instrument containing information regarding demographic characteristics, knowledge of HCV and attitudes towards patients with HCV infection. Descriptive statistics, Fisher's exact test, Student's t-tests, Mann–Whitney U-test and multiple logistic regression (MLR) were carried out (P < 0.05 was considered significant). Results: Response rate was 90% (n = 306), and more than half (54%, n = 165) of participants had high knowledge level (above the mean); 97.7% (n = 299) demonstrated positive attitudes. MLR showed that high knowledge of dental students regarding HCV was substantially influenced by advancement in year of study (last year; P < 0.001) and type of university (federal; P = 0.049). Positive attitude towards HCV-infected patients was mainly influenced by age (P = 0.004) and male gender (P = 0.022). Conclusions: These results demonstrated a satisfactory knowledge about HCV infection amongst dental students, but some gaps were observed, suggesting the importance of continuous education about HCV in this population to prevent HCV infection as well as discrimination and prejudice towards patients with hepatitis C.
Keywords: attitudes; dental students; hepacivirus; hepatitis C; knowledge; practices